Sistem maklumat geografi II - A. Kadir, Abd. Majid; Omar, Abdullah Hisam (Universiti Teknologi Malaysia, 2005)
GIS software, introduction, the evolution of GIS software, architecture of GIS software, types of GIS software systems, lecture 2 geographic data modelling, introduction, GIS data models, example of water facility object data model, geographic data modeling in practice, lecture 3 GIS data collection, introduction, primary geographic data capture, secondary geographic data capture, obtaining data from external sources, capturing attribute data, managing a data capture project, lecture 4 creating and maintaining geographic, databases, introduction, database management systems, storing data in DBMS tables, geographic database types and functions, geographic database design, structuring geographic information, editing and maintenance, multi-user editing of continuous databases.